A randomised controlled trial to enhance travel-related physical activity: A pilot study in patients with coronary heart disease. (June 2022) - Batool, Tooba; Neven, An; Smeets, Christophe JP.; Scherrenberg, Martijn; Dendale, Paul; Vanrompay, Yves; Adnan, Muhammad; Ross, Veerle; Brijs, Kris; Wets, Geert; Janssens, Davy
Abstract: Introduction: Patients suffering from coronary heart disease (CHD) are frequently less active. Physical Activity (PA) could be increased through changes in routine travel behaviour. Achieving a certain PA amount is essential in the secondary prevention of CHD patients. Objective: This study combines objective monitoring together with an intervention using advanced Information, Communication and Technology means in a framework to improve travel-related PA. This paper aims to describe an integrated research framework and tests the effectiveness of a theory-based (Trans-theoretical Model, TTM) intervention. Methods: A pilot Randomised Controlled Trial (70:30) was conducted in Belgium. Participating patients attended a preparatory work session intended to get their demographic information, assess their Stage of Change, and learn using a smartphone app (developed to monitor travel behaviour). After the work session, patients in the experimental group were monitored for three weeks and then received a customized feedback report. After feedback, the patients were monitored for another three weeks; while patients in the control arm were continuously monitored for 6 weeks without an intermediate feedback report. At the end of the study period, both groups received their feedback report. Results: The data of 25 patients were used in the trial, of which 18 were in the experimental group. The outcome measure used was the Active Travel Score (ATS), i.e. the PA achieved by walking and cycling trips. A significant ( p < 0.05 ) positive increase in ATS ( X ‾ = 14.2, 95 %, CIs = 2.1 − 26.4 ) was observed after the intervention. Multiple pairwise comparisons confirmed that the effect of the intervention lasted for a week, indicating an important short-term effect. Conclusion: Objective monitoring and TTM-based interventions can be useful to provide a low-cost solution to achieve an increase in PA in secondary prevention of cardiac patients. Although these results are promising, RCTs with larger sample sizes are required to confirm the current findings. Highlights: RCT to enhance physical activity (PA) by objective travel monitoring and tailored feedback. A significant increase in travel-related PA is seen in CHD patients. The intervention effect lasted for a week (short-term). Enhancing travel-related PA can be promising in the prevention therapies of CHD patients.